Ijtihad and Istinbath Methods of Imam Ahmad Bin Hambal's Law, and Their Implementation in Sharia Economics and Finance - Rabiatul Adawiyah (Jurnal Impresi Indonesia, 2025)
The method of ijtihad and legal istinbath developed by Imam Ahmad bin Hambal, as well as its application in the context of sharia economics and finance. Imam Ahmad bin Hambal, as one of the great figures in the history of Islamic thought, is known for his conservative approach to the source of law, focusing on the Qur'an and the Sunnah. Through in-depth analysis, this paper shows how the principles proposed by Imam Ahmad can be implemented in various aspects of Islamic economics and finance, including in the development of Islamic financial products that are in accordance with Islamic law. Using the latest data and statistics, as well as relevant case studies, this study aims to provide a deeper insight into the relevance of Imam Ahmad's method in the modern context, as well as the challenges and opportunities that exist in its application in the world of Islamic finance.